Applications of Mash-ups for a Digital Journal - Muhammad Salman, Khan; Kulathuramaiyer, Narayanan; Maurer, Hermann (Journal of Universal Computer Science, 2008)
The WWW is currently experiencing a revolutionary growth due to numerous emerging tools, techniques and concepts. Digital journals thus need to transform themselves to cope with this evolution of the web. With their growing information size and access, conventional techniques for managing a journal and supporting authors and readers are becoming insufficient. Journals of the future need to provide innovative administrative tools in helping its managers to ensure quality. They also need to provide better facilities for assisting authors and readers in making decisions regarding their submission of papers and in providing novel navigational features for finding relevant publications and collaborators in particular areas of interest. In this paper, we explore an innovative solution to address these problems by using an emerging Web 2.0 technology. We explore the application of mash-ups for J.UCS - the Journal of Universal Computer Science and encourage readers and authors to try out the applications (see section 11 Conclusions). J.UCS can then serve as a model for contemporary electronic journals.